A Review on Mixed Reality Operating Systems : Current Trends, Challenges and Prospects - Suresh Vakkalanka (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the rapidly evolving landscape of Mixed Reality (MR) operating systems, examining their core functionalities, architectural components, and the cutting-edge trends shaping their development. The article provides an in-depth analysis of the challenges facing MR OS developers, including interoperability, scalability, and user experience optimization, while offering insights into potential solutions. A comparative article of leading MR platforms highlights the diverse approaches and capabilities within the current ecosystem. The article delves into future prospects, discussing the integration of artificial intelligence, advanced user interaction paradigms, and their potential impact across various industries. Additionally, it addresses strategies for overcoming current limitations and explores the broader implications of MR technology on society, including ethical considerations and privacy concerns. By synthesizing current research and industry developments, this paper offers a comprehensive overview of the state of MR operating systems, their potential applications, and the transformative role they are poised to play in shaping human-computer interaction and digital experiences. The article concludes by emphasizing the critical importance of continued innovation in MR operating systems for advancing the field and realizing the full potential of mixed reality technology in both personal and professional domains.